A Descriptive Study about Factors Affecting Data Quality of EWARS in Surabaya 2016 - Sobhita Paramita (Jurnal Berkala Epidemiologi, 2017)
Early Warning Alert and Response System (EWARS) is a health information technology that is used for recording and reporting diseases especially those that have the potential to cause outbreaks and can produce "alerts" if an outbreak indication is found in an area. EWARS reporting is carried out on a weekly basis by reporting disease data on the EWARS website according to the code of each predetermined disease. This research is a descriptive study with a quantitative approach. The sampling technique uses simple random sampling. Interviews were conducted with 33 EWARS officers at the Public Health Center (PHC) in Surabaya using a questionnaire. Research variables are staff characteristics including age, gender, level of education, length of work, experience using the computer, and the experience of obtaining EWARS socialization as well as the level of knowledge, attitudes, perceptions of ease, and perceived usefulness of officers regarding the implementation of EWARS, and the quality of EWARS report data at Surabaya City in 2016. The results of this study indicate that the majority of respondents are aged 20-40 years, are female, have an adequate level of education, have worked as EWARS officers for more than 2 years, have used computers for more than 2 years, and the majority had received EWARS socialization. Most respondents have a good level of knowledge, attitudes, and perceptions of ease and usefulness of technology regarding the implementation of EWARS, but the quality of the data produced is of poor quality. The conclusion of this study is the level of knowledge, attitudes, perceptions of ease, and the perception of usefulness is good but it doesn't follow by a quality EWARS report. EWARS reports that are sent in full and on time are not necessarily of quality because there are still other attributes that need to be measured.